2015
DOI: 10.1002/14651858.cd010664.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioural treatment for subacute and chronic neck pain

Abstract: Analysis 3.9. Comparison 3 CBT versus other types of treatment (chronic NP), Outcome 9 Coping (intermediate-term follow-up

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 98 publications
0
33
0
3
Order By: Relevance
“…This may not be so surprising because our behavioral approach was based on Cognitive Behavioural Therapy (CBT) principles, and a recent review of CBT treatment on chronic pain patients [32] concluded that CBT in addition to another interventions did not result in significantly better results. Moreover, the review showed only evidence for a short-time effect.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be so surprising because our behavioral approach was based on Cognitive Behavioural Therapy (CBT) principles, and a recent review of CBT treatment on chronic pain patients [32] concluded that CBT in addition to another interventions did not result in significantly better results. Moreover, the review showed only evidence for a short-time effect.…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts the traditional view, considering neck and shoulder pain as more stress-related than extremity pain [ 3 , 4 , 13 , 17 ]. This assumption resulted in an increased focus on cognitive-behavioral treatments for the presumed stress-related musculoskeletal pain conditions, showing a lack of success [ 61 , 62 ]. The findings in this study underscores the importance of a comprehensive understanding of pain mechanisms in young people, as well as more appropriate and effective treatment and prevention approaches for this group.…”
Section: Discussionmentioning
confidence: 99%
“…Each physiotherapist received a half day practical training session with the project leader with written and oral communications on the rehabilitation programme. The structured physiotherapy programme was based on the management of other neck pain disorders, and included both a neuromuscular training component and a cognitive‐behavioural component (Gross et al, ; Monticone et al, ). The neuromuscular training component started with retraining the activation of the deep neck muscles, which progressed into isometric and dynamic exercises focused on improving the pattern and endurance of neck muscle activation.…”
Section: Methodsmentioning
confidence: 99%